PENGARUH PENGETAHUAN DAN SIKAP MASYARAKAT TERHADAP PELAKSANAAN PROTOKOL KESEHATAN SAAT PANDEMIK COVID-19 DI KECAMATAN SARUDIK KABUPATEN TAPANULI TENGAH - ahmad Sungadi; Reisy Tane (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2022)
The Covid-19 pandemic is an event that spread of the 2019 corona virus disease around the world. Basically the spread of the virus (corona) is classified as very fast and makes it easier for humans on earth to be infected more quickly by the virus outbreak. Although the WHO, the Centers for Disease Control and Prevention (CDC) and the Indonesian Ministry of Health have issued a lot of actual information and guidelines related to Covid-19, many people do not understand it properly. This study aims to explain the influence of public knowledge and attitudes towards the implementation of health protocols during the Covid-19 pandemic in Sarudik District, Central Tapanuli Regency. This research is an observational analytic study using a cross sectional design. Sarudik District, Central Tapanuli Regency is the location where this research was conducted. The population in this study were all people in Sarudik District with a sample of 90 people. Data were collected using primary data and secondary data and analyzed using the chi square test with a 95% confidence level. The results showed that there was an influence of knowledge and attitudes on the implementation of health protocols during the Covid-19 pandemic in Sarudik District, Central Tapanuli Regency (p = 0.014 and p = 0.008). It is hoped that related parties such as the health office, village and community in Sarudik District, Central Tapanuli Regency can maximize education about health protocols as an effort to increase knowledge, attitudes and actions in implementing health protocols, maximize programs with an intra-personal approach so that each individual becomes aware and responsive to the implementation of health protocols as well as making policies related to sanctions for people who do not comply with health protocols in Sarudik District, Central Tapanuli Regency